Β-FeOOH modified polyurethane foam for efficient adsorption of arsenite and arsenate from contaminated water - Qiang Li; Yifan Yao; Yingying Tang; Jinsheng Huang; Mei He; Wei Zhang (Results in Chemistry)
The prevalent issue of arsenic (As) contamination in groundwater and drinking water has become a significant global concern. While metal oxide-modified polyurethane foam (PUF) provides a cost-effective solution for arsenite [As(III)] and arsenate [As(V)] removal, the absorption mechanism by akaganeite iron oxy hydroxide β-FeOOH-PUF and its practical applications remains understudied. This investigation concentrates on the synthesis of β-FeOOH-PUF through the co-precipitation method utilizing iron chloride (FeCl3) and polyethyleneimine (PEI) as raw materials. In the quest to purify contaminated natural water sources, β-FeOOH-PUF has been employed to adsorb As(III) and As(V). Findings demonstrate successful iron deposition on the foam's surface, generating numerous positively charged FeO groups. Furthermore, the specific surface area (SSA) of β-FeOOH-PUF exceeded that of the unmodified PUF. Adsorption kinetics and isothermal adsorption analyses revealed a chemical adsorption mechanism for both As(III) and As(V) on a monolayer, with maximum adsorption capacities of 7.37 and 7.96 mg g−1, respectively. The pH range had minimal impact on adsorption efficiency, with β-FeOOH-PUF demonstrating superior performance over unmodified PUF in removing As(III) and As(V) across various pH levels. The increase in the concentrations of Cl−, SO42−, HCO3−, NO3−, and PO43− will compete for adsorption sites, change surface charge density, and significantly hinder the adsorption of As(V) by β-FeOOH-PUF. β-FeOOH-PUF can be regenerated under H2O, acidic, and alkaline conditions, offering a novel approach to treat inorganic As-contaminated water sources. Therefore, due to its abundant FeO functional groups, substantial SSA, and recyclability, β-FeOOH-PUF emerges as a highly promising adsorbent for inorganic As(III) and As(V) removal.